Lithium ion battery active substance modified by bacterial cellulose and preparation method of lithium ion battery active substance
Through bacterial cellulose modification treatment and high-voltage homogenizer technology, the lithium-ion battery active materials are coated, which solves the problem of volume expansion and insufficient conductivity of the lithium-ion battery active materials, and significantly improves the mechanical properties and cycle stability of the battery.
Patent Information
- Application Number
- CN202411993011.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
In applications, lithium-ion battery active materials have problems such as volume expansion, insufficient conductivity and poor circulation performance, which affect the capacity performance and circulation stability of the battery.
Through bacterial cellulose modification treatment, lithium-ion battery active materials are coated, and a high-pressure homogenizer and hydrothermal carbonization treatment technology are used to form a network structure to limit the volume expansion of the active material and improve conductivity.
It effectively improves the volume expansion and insufficient conductivity of the active materials of lithium-ion batteries, improves the mechanical properties and cycle stability of the batteries, and reduces production costs.
Smart Images

Figure CN119764417A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery active materials, and in particular relates to a lithium ion battery active material treated by bacterial cellulose modification and a preparation method thereof. Background Art
[0002] Lithium-ion batteries can be widely used in consumer electronics, energy storage, electric vehicles and other fields due to their advantages such as high energy density, long cycle life, low self-discharge rate and no memory effect. The positive electrode materials of lithium-ion batteries mainly include layered positive electrode materials, spinel positive electrode materials and polyanion positive electrode materials; the negative electrode materials mainly include carbon negative electrode materials, silicon-based negative electrode materials and other negative electrode materials. When these active materials are used in lithium-ion batteries, there are problems such as volume expansion, insufficient conductivity, and easy material detachment, which affect the capacity and cycle stability of lithium-ion batteries.
[0003] Bacterial cellulose is a new type of material that is a combination of traditional cellulose materials and nanotechnology. It inherits the basic structure of natural cellulose and good biocompatibility. At the same time, due to its nanoscale size, bacterial cellulose also has the characteristics of high strength, large specific surface area, good stability, good optical transparency and easy to interweave into a network structure. These characteristics make bacterial cellulose-based materials have good application prospects in lithium-ion batteries, and are expected to form a network structure to limit the volume expansion of active materials and improve mechanical properties. In addition, through carbonization treatment, carbon materials derived from bacterial cellulose show high conductivity and can also be used to improve the performance of lithium-ion batteries. At present, the application methods of bacterial cellulose in batteries are limited. Therefore, it is necessary to explore simpler, more efficient and scalable methods for the application of bacterial cellulose in lithium battery slurry to reduce production costs and achieve large-scale applications. Summary of the invention
[0004] The purpose of the present invention is to provide a lithium ion battery active material modified by bacterial cellulose, which improves the volume expansion and insufficient conductivity of the active material and improves the battery performance. The synthesis conditions are simple, the raw materials are highly safe and low in price, and it meets the requirements of industrial production.
[0005] The present invention also aims to provide a method for preparing the above-mentioned bacterial cellulose modified lithium ion battery active material.
[0006] A lithium-ion battery active material modified by bacterial cellulose, composed of the following weight percentages: 80%-99.99% of lithium-ion battery active material, 0.01%-20% of bacterial cellulose or its carbonized derivative, wherein the bacterial cellulose or its carbonized derivative is treated and coated on the surface of the lithium-ion battery active material. Preferably, the weight percentages of bacterial cellulose or its carbonized derivative and active material in the active material are 95%-99.5% and 0.5%-5%, respectively.
[0007] Furthermore, the preparation method includes the following:
[0008] The bacterial cellulose and deionized water are prepared into a bacterial cellulose solution;
[0009] The bacterial cellulose solution is directly mixed with the active material, or the bacterial cellulose solution is first subjected to hydrothermal carbonization treatment and then mixed with the active material;
[0010] The obtained mixture was homogenized by a high pressure homogenizer and then dried.
[0011] Furthermore, the hydrothermal carbonization treatment is a hydrothermal treatment at 180-200° C. for 300-900 minutes.
[0012] Furthermore, the high-pressure homogenization is a homogenization treatment performed at 20-200 bar for 1-500 min.
[0013] The active material may be graphite, silicon, silicon oxide, silicon carbon or other negative electrode materials for lithium ion batteries; or lithium cobalt oxide, lithium nickel oxide, ternary nickel cobalt manganese / aluminum, lithium manganese oxide, lithium iron phosphate or other positive electrode materials for lithium ion batteries.
[0014] The active material is mixed with a binder and a conductive agent by a conventional method to prepare a pole piece slurry, wherein the binder can be polyvinyl alcohol, polytetrafluoroethylene, polyolefin, polyvinylidene fluoride, polyurethane, polyacrylic acid, styrene-butadiene rubber, sodium carboxymethyl cellulose, sodium alginate or other binders.
[0015] The bacterial cellulose is of nanometer-scale diameter and micrometer-scale length.
[0016] The beneficial effects of the present invention are described in detail as follows:
[0017] (1) The present invention provides an active material modified by bacterial cellulose, which is applied to lithium-ion batteries and effectively improves the problems of volume expansion, insufficient conductivity, and poor cycle performance of active materials in lithium-ion batteries. By treating the bacterial cellulose with a high aspect ratio to effectively wrap the active material, the volume expansion of the active material is limited, and the mechanical properties of the electrode can be effectively improved, thereby improving the cycle stability of the lithium battery.
[0018] (2) The bacterial cellulose is subjected to hydrothermal carbonization treatment so that it retains mechanical strength while having a certain conductivity, which can expand the conductive network and promote the capacity of the battery.
[0019] (3) After high-pressure homogenization treatment, bacterial cellulose with a diameter of nanometers and active materials can achieve network structure and effective coating at the same time. It can be clearly seen that the cellulose network is more evenly wrapped on the active material, with a more excellent effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a comparison chart of the active material SIC1200 before and after modification with bacterial cellulose.
[0021] Figure 2 In Example 1, sodium carboxymethyl cellulose and styrene-butadiene rubber were used as binders, and the mass loading of the active material SIC1200 was about 1 mg cm -2 Discharge curve and cycle performance diagram of silicon-carbon electrode.
[0022] Figure 3 For Example 1 and Comparative Examples 1.1 to 1.5, sodium carboxymethyl cellulose and styrene-butadiene rubber were used as binders, and the mass loading of active material SIC1200 was about 1 mg cm -2 Comparison of discharge curves of silicon-carbon electrodes.
[0023] Figure 4 This is a comparison chart of the thickness of the pole pieces of Comparative Example 1.1 and Comparative Example 1.3 before and after cycling.
[0024] Figure 5 For Example 2, Comparative Examples 2.1 and 2.2, polyacrylic acid (degree of polymerization 1.25 million) was used as a binder, and the mass loading of the active material SIC1200 was about 1 mg cm -2 Comparison of discharge curves of silicon-carbon electrodes.
[0025] Figure 6 This is a comparison chart of bacterial cellulose before and after hydrothermal carbonization treatment.
[0026] Figure 7 This is an electron microscope image of the active material SIC1200 coated with bacterial cellulose after hydrothermal carbonization. DETAILED DESCRIPTION
[0027] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0028] Example 1
[0029] This example prepares an active substance modified from bacterial cellulose.
[0030] A bacterial cellulose-modified lithium ion battery active material is composed of the following substances in percentage by weight: 98% of active material SIC1200 and 2% of bacterial cellulose.
[0031] The preparation method of the above-mentioned bacterial cellulose modified lithium ion battery active material is carried out according to the following steps:
[0032] (1) Select commercial bacterial cellulose solution.
[0033] (2) Further, the bacterial cellulose in step (1) and deionized water are mixed in a certain ratio to form a bacterial cellulose solution with a solid content of 1%.
[0034] (3) Further, 2 g of the bacterial cellulose solution treated in step (2) was mixed evenly with 0.98 g of the active material SIC1200.
[0035] (4) Further, the mixture in step (3) is homogenized by a high pressure homogenizer at 200 bar for 5 min, and dried to prepare.
[0036] The silicon-carbon active material modified by bacterial cellulose prepared by the present invention is used as the negative electrode active material of lithium ion battery, and the remaining steps of the preparation method of the negative electrode are the same as the usual preparation method. The preparation method of the pole piece is as follows: the modified active material, the binder sodium carboxymethyl cellulose and styrene-butadiene rubber (wherein the mass ratio of sodium carboxymethyl cellulose and styrene-butadiene rubber is 1:1), and the conductive agent Super P are mixed evenly in a mass ratio of 8:1:1 to prepare a slurry. The slurry is coated on the copper current collector, and the coated pole piece is placed in a vacuum oven at 100°C and dried for 12 hours. 1M LiPF6 is dissolved in ethylene carbonate (EC) and dimethyl carbonate (DMC) as the electrolyte, the lithium sheet is the negative electrode, Celgard 2325 is the diaphragm, and CR 2025 stainless steel is the battery shell to assemble into a button lithium ion battery.
[0037] Comparative Example 1.1
[0038] This comparative example prepares an active substance modified by bacterial cellulose. The difference from Example 1 is that step (4) is missing, that is, the mixed bacterial cellulose and active material are directly dried without homogenizing using a high-pressure homogenizer. The rest of the specific process is carried out with reference to Example 1.
[0039] Comparative Example 1.2
[0040] This comparative example prepares an active substance. The difference from Example 1 is that step (1) and step (2) are missing, and the bacterial cellulose solution in step (3) is replaced by deionized water, that is, no bacterial cellulose is added. The rest of the specific process is carried out with reference to Example 1.
[0041] Comparative Example 1.3
[0042] This comparative example prepared an active substance modified by bacterial cellulose. The active substance was composed of the following weight percentages: 99% active substance SIC1200, 1% bacterial cellulose, that is, the bacterial cellulose solution in step (3) was 1g, and the active material SIC1200 was 0.99g. The rest of the specific process was carried out with reference to Example 1.
[0043] Comparative Example 1.4
[0044] This comparative example prepared an active substance modified by bacterial cellulose. The active substance was composed of the following weight percentages: 99.5% of active substance SIC1200, 0.5% of bacterial cellulose, that is, in step (3), the bacterial cellulose solution was 0.5g, and the active material SIC1200 was 0.995g. The rest of the specific process was carried out with reference to Example 1.
[0045] Comparative Example 1.5
[0046] This comparative example prepared an active substance modified by bacterial cellulose. The active substance was composed of the following weight percentages: 95% of active substance SIC1200, 5% of bacterial cellulose, that is, the bacterial cellulose solution in step (3) was 5g, and the active material SIC1200 was 0.95g. The rest of the specific process was carried out with reference to Example 1.
[0047] like Figure 1 As shown, a) and b) are electron micrographs of SIC1200 before treatment, c) and d) are electron micrographs of SIC1200 after treatment in the manner of Comparative Example 1.1, and e) and f) are electron micrographs of SIC1200 after modification in the manner of Example 1. All the figures are randomly selected, and the overall morphology in each example is basically as shown in the corresponding figure. It can be seen that bacterial cellulose and active substance SIC1200 can obtain a good coating modification effect after mixing and high-pressure homogenization treatment, and bacterial cellulose obviously presents a network structure and is coated on the surface of the active substance, while no effective coating is formed in other schemes.
[0048] like Figure 2 As shown in the figure, when the active material mass loading is 1 mg cm -2 At a rate of 0.03C, the first cycle of Example 1 showed 950 mAh g -1The discharge capacity and the first cycle coulombic efficiency of up to 86.3% are still 542mAh g after further cycling at 0.2C rate for 100 cycles. -1 The surface capacity and capacity retention rate are as high as 71.1%.
[0049] like Figure 3 As shown, when Example 1 is compared with Comparative Example 1.1, the discharge capacity of the battery after high-pressure homogenization of bacterial cellulose and SIC1200 in Example 1 is significantly better than that of Comparative Example 1.1 without homogenization. At the same time, when Example 1 is compared with Comparative Examples 1.2 to 1.5, when the mass ratio of bacterial cellulose to active material is different, the battery exhibits different discharge capacity. When the mass loading of active material is 1 mg cm -2 When the activation rate is about 0.03C for 2 cycles, and the discharge specific capacity is further cycled at 0.2C for 100 cycles, the order from large to small is: Example 1, Comparative Example 1.3, Comparative Example 1.4, Comparative Example 1.5, Comparative Example 1.2. As can be seen from the above, when the amount of bacterial cellulose dry matter is 0.5% to 5% during the modification of the active material, the capacity of the silicon-carbon negative electrode of the lithium battery is better than that of Comparative Example 1.2 which has not been coated with bacterial cellulose.
[0050] like Figure 4 As shown, a) is the electron micrograph of the negative electrode of comparative example 1.2 before cycling, and the thickness of the electrode sheet is 20.4μm; c) is the electron micrograph of the negative electrode of comparative example 1.2 after cycling 800 times at a rate of 0.2C, the thickness of the electrode sheet is 33.7μm, and the expansion rate of the electrode sheet is 65.2%. b) is the electron micrograph of the negative electrode of embodiment 1 before cycling, and the thickness of the electrode sheet is 22.3μm; d) is the electron micrograph of the negative electrode of embodiment 1 after cycling 800 times at a rate of 0.2C, the thickness of the electrode sheet is 29.2μm, and the expansion rate of the electrode sheet is 30.9%. Compared with comparative example 1.2 of the active material that has not been modified with bacterial cellulose, the expansion rate of the electrode sheet of embodiment 1 with a dry matter amount of bacterial cellulose in the active material of 2% after cycling decreased by 52.6%. It can be seen that the active material modified with bacterial cellulose helps to limit the expansion of the electrode sheet.
[0051] Example 2
[0052] This example prepares an active substance modified from bacterial cellulose.
[0053] A bacterial cellulose-modified lithium-ion battery active material is composed of the following substances in percentage by weight: 98% of active material SIC1200 and 2% of hydrothermal carbonized bacterial cellulose.
[0054] The preparation method of the above-mentioned bacterial cellulose modified lithium ion battery active material is carried out according to the following steps:
[0055] (1) Select commercial bacterial cellulose solution.
[0056] (2) Further, the bacterial cellulose in step (1) and deionized water are mixed in a certain ratio to form a bacterial cellulose solution with a solid content of 1%.
[0057] (3) Further, the 1% bacterial cellulose solution in step (2) was subjected to a hydrothermal carbonization treatment at 200 degrees Celsius for 900 minutes.
[0058] (4) Further, 2 g of the bacterial cellulose solution treated in step (3) was mixed evenly with 0.98 g of the active material SIC1200.
[0059] (5) Further, the mixture in step (4) is homogenized by a high pressure homogenizer at 200 bar for 5 min, and dried to prepare.
[0060] The silicon-carbon active material modified by bacterial cellulose prepared by the present invention is used as the negative electrode active material of the lithium ion battery, and the remaining steps of the preparation method of the negative electrode are the same as the usual preparation method. The preparation method of the pole piece is as follows: the modified active material, the binder polyacrylic acid (polymerization degree 1.25 million), and the conductive agent Super P are mixed uniformly in a mass ratio of 8:1:1 to form a slurry. The slurry is coated on the copper current collector, and the coated pole piece is placed in a vacuum oven at 100°C and dried for 12 hours. 1M LiPF6 is dissolved in ethylene carbonate (EC) and dimethyl carbonate (DMC) as the electrolyte, the lithium sheet is used as the negative electrode, Celgard2325 is used as the diaphragm, and CR 2025 stainless steel is used as the battery shell to assemble into a button lithium ion battery.
[0061] Comparative Example 2.1
[0062] This comparative example prepares an active substance. The difference from Example 2 is that step (1), step (2), and step (3) are missing, and in step (4), the bacterial cellulose solution is replaced by deionized water, that is, no bacterial cellulose is added. The rest of the specific process is carried out with reference to Example 1.
[0063] Comparative Example 2.2
[0064] This comparative example prepared a lithium-ion battery slurry with bacterial cellulose added. The difference from Example 2 is that the hydrothermal carbonization conditions in step (3) are different, that is, the hydrothermal carbonization treatment is carried out at 180 degrees Celsius for 300 minutes. The rest of the specific process is carried out with reference to Example 2.
[0065] like Figure 5 As shown in the figure, when the active material mass loading is 1 mg cm -2 At a rate of 0.03C, the first cycle of Example 2 showed 919 mAh g-1 The discharge capacity and the first cycle coulomb efficiency of 83.9% are still 501mAh g after further cycling at 0.2C rate for 100 cycles. -1 The surface capacity of the battery was 1.37W, and the capacity retention rate was as high as 69.2%. Comparing Example 2 and Comparative Example 2.2 with Comparative Example 2.1, the capacity and cycle performance of the lithium battery after the active material was modified with bacterial cellulose were better than those of Comparative Example 2.1 without treatment. Among them, the battery capacity of Example 2, in which the hydrothermal carbonization temperature of bacterial cellulose was higher and the time was longer, was better than that of Comparative Example 2.2.
[0066] like Figure 6 As shown, the bacterial cellulose maintains a fiber structure with a length of micrometers and a diameter of nanometers before and after hydrothermal carbonization treatment, and can be interwoven to form a network structure to cover the active material.
[0067] like Figure 7 As shown, the bacterial cellulose after hydrothermal carbonization also has a good coating effect on the active materials.
Claims
1. A lithium ion battery active material modified by bacterial cellulose, characterized in that: The invention is composed of the following substances: a lithium-ion battery active material, and bacterial cellulose or a carbonized derivative thereof; wherein the bacterial cellulose or the carbonized derivative thereof is treated and coated on the surface of the lithium-ion battery active material.
2. The lithium ion battery active material modified by bacterial cellulose according to claim 1, characterized in that: The preparation method thereof comprises the following steps: The bacterial cellulose and deionized water are prepared into a bacterial cellulose solution; The bacterial cellulose solution is directly mixed with the active material, or the bacterial cellulose solution is first subjected to hydrothermal carbonization treatment and then mixed with the active material; The obtained mixture was homogenized by a high pressure homogenizer and then dried.
3. The lithium ion battery active material modified by bacterial cellulose according to claim 2, characterized in that: The weight percentages of bacterial cellulose or its carbonized derivative and active material in the active substance are 80%-99.99% and 0.01%-20% respectively.
4. The lithium ion battery active material modified by bacterial cellulose according to claim 2, characterized in that: The weight percentages of bacterial cellulose or its carbonized derivative and active material in the active substance are 95%-99.5% and 0.5%-5% respectively.
5. The lithium ion battery active material modified by bacterial cellulose according to claim 2, characterized in that: The hydrothermal carbonization treatment is a hydrothermal treatment at 180-200° C. for 300-900 minutes.
6. The lithium ion battery active material modified by bacterial cellulose according to claim 2, characterized in that: The high pressure homogenization is a homogenization process performed at 20-200 bar for 1-500 min.
7. The lithium ion battery active material modified by bacterial cellulose according to claim 1, characterized in that: The active material is a negative electrode material of a lithium ion battery or a positive electrode material of a lithium ion battery.
8. A lithium ion battery electrode material, characterized in that: The active material according to any one of claims 1 to 7 is mixed with a binder and a conductive agent to obtain an electrode slurry.
Citation Information
Patent Citations
Lithium ion battery and preparation method thereof
CN102637898A
Preparation method for nanocrystal cellulose composite material, product and application thereof
CN104629276A
Bacterial cellulose membrane / porous carbon adsorbent and preparation thereof
CN104722285A
Three-dimensional mesh structure form electrode for electrochemical device, method for producing same, and electrochemical device comprising same
CN107873104A
Nano modified composite material and preparation method and application thereof
CN113248868A